POLA KOMUNIKASI INTERPERSONAL KORBAN TRAFFICKING PENGANTIN PESANAN DI SINGKAWANG KALIMANTAN BARAT - Elly Triana; Christina Rochayanti; Isbandi Isbandi (Jurnal Ilmu Komunikasi, 2009)
Trafficking is slavery activity of including in human being commerce, one of the typical modus which during the time trend in Kalbar, that is “order bride”. The brokers look for the beautiful women in Singkawang Town, especially amoy-amoy to be married with the foreign citizen men, Taiwan, Hongkong, and Singapore. Amount of informan is five people. Research method used by descriptive qualitative, this method giving description and communications analyse between individual in relation between perpetrator of order bride with the brokers/ middleman. Accumulation data technique used by Observation, Interview, and reference study technique for the perception, obtaining information, and collect the data, adding data, support- ing data from other sources. The results of this research indicated that pattern of interpersonal communications in relation of order brige with the brokers/middleman done by approach every order bridge started with the introduction, continued with the dating, dating intensity, and com- munications of one-way, two-way, feedback, and persuasive. All this represent the important matter in making and looking after good cooperation or relation.